Cuantificación de la generación de residuos sólidos orgánicos de la crianza de porcinos, para proceso de valoración en la facultad de agronomía. San Juan. 2019 - Diaz Murayari, Oriana Juneth (2022)
The objective of this thesis work was to quantify the generation of organic solid waste (swine manure) generated in the swine teaching and research project of the Faculty of Agronomy of the National University of the Peruvian Amazon (FA-UNAP), in order to implement assessment processes within the pig project, evaluating a total population of 80 pigs. The information was collected from the primary source that included data collected from the evaluation of all the project pens, likewise, it included the participation of workers from the project and a group of 6 students from the engineering career in environmental management. At the end of the evaluation, it was found that the level of food consumed by the pigs within the project is 130 kg/day, and in terms of generation per capita animal per day for each pen; in the case of corral No. 01, an average of 0.302 kg/animal/day was obtained, obtaining a generation of 0.0054 Tm/day, 0.1620 Tm/month and 1.9710 Tm/year; followed by corral No. 02 with a per capita generation of 1.0393 kg/animal/day, with a generation of 0.0644 Tm/day, 1.9320 Tm/month and 23.1840 Tm/year; likewise, with respect to the generation of leachate product of the cleaning of the pens after the collection of excreta, a generation of 776 Lt/day was determined with a projection of 23,280 Lt/month and 283,240 Lt/year.